(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Cultural institutions, specifically theatres, which are the main focus of this research paper, are struggling to find the best way to approach and attract the audience, in particular the young audience (in this case Generation Y). The authors of the paper believe that unconventional marketing has potential as a tool of communication with the audience in terms of both future research and practical application. Unconventional marketing can be used for the benefit of not only the theatres, but also the whole society by building a theatre audience and in general by raising awareness of the role cultural institutions play in the economic development of a country. Based on empirical research of city and national theatres in the Republic of Croatia, the objective of this paper was to identify and understand unconventional marketing and determine if it can be a useful marketing tool for communication with Generation Y. The research focused on two types of theatres (i.e. city and national theatres) and comprised two surveys, one for theatre employees, n=41, and the other for Generation Y, n=285. Research hypotheses were focused on analysing the effectiveness of both promotional methods used by the theatres and unconventional marketing targeting Generation Y. Research results indicate that theatres have not adapted their promotional activities to Generation Y. However, they also show that unconventional marketing has great potential in both groups with respect to theatre events. Psychometric analysis confirmed the good metric properties of the proposed Theatre PUMA Scale, which measures the potential of unconventional theatre marketing.